Fire-resistant iron-based phosphates/phosphorus-doped carbon composites derived from phytic acid-treated metal organic frameworks as high-efficiency microwave absorbers. (5th November 2022) - Liu, Jue; Meng, Can; Liu, Qingwei; Li, Nailin; Yu, Ronghai; Zeng, Min
Abstract: Considering the electromagnetic pollution in harsh environments, it is vital to prepare multifunctional microwave absorbers to broaden their application fields. Herein, fire-resistant iron-based phosphates/phosphorus-doped carbon composites were annealed from phytic acid-treated metal organic frameworks. Through tailoring the dosage of phytic acid used in the preparation process, composites with diverse morphologies, crystal structures, electric and microwave absorption properties are obtained. When the dosage of phytic acid used reaches 4 mL, the obtained composite, Fe2 P4 O12 /phosphorus-doped carbon, possesses the best microwave absorption performance with a minimum reflection loss of −67.6 dB (2.0 mm) and an effective absorption bandwidth of 5.76 GHz (2.1 mm, 12.24–18 GHz). The microwave attenuation could be mainly attributed to the high conductivity brought by phosphorus-doped carbon, and polarization relaxations triggered by dipoles, functional groups, and unbalanced charges at interfaces. Specifically, the charge density distribution, obtained with density functional theory (DFT), suggests the occurrence of intense charge transfer and formation of internal electric field at P-carbon, O-carbon, and iron-based phosphates/phosphorus-doped carbon interfaces. Meanwhile, the as-prepared iron-based phosphates/phosphorus-doped carbon composites possess good fire-resistant property. The work provides a novel idea to construct multifunctional materials with high-efficient microwave absorption to broaden their application fields. Graphical abstract: Image 1 Highlights: Facile synthesis of iron-based phosphates/phosphorus-doped carbon composites. Compositions can be regulated by tailoring the dosage of phytic acid used to treat the precursor. A minimum R L of −67.6 dB (2.0 mm) and an EAB of 5.76 GHz (2.1 mm, 12.24–18 GHz) is achieved. High conductivity and strong polarization contribute to microwave absorption. The composites demonstrate excellent fire-resistant property.